2017
DOI: 10.5505/tjtes.2017.23539
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin exhibit supportive effects on oxidants and anastomotic healing during intestinal ischemia reperfusion injury

Abstract: BACKGROUND:The aim of this study was to investigate the effects of melatonin on intestinal anastomosis after intestinal ischemia/ reperfusion injury (IRI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…12 Of note, melatonin protects against ischemia-reperfusion injury in the kidney, intestine, and heart in normoglycemic animal models. [13][14][15] Recent studies have found the same beneficial effects in hyperglycemic rats' hearts and kidneys. 16,17 Emerging evidence demonstrates the neuroprotective effects of melatonin in normoglycemic animals with focal cerebral ischemia.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…12 Of note, melatonin protects against ischemia-reperfusion injury in the kidney, intestine, and heart in normoglycemic animal models. [13][14][15] Recent studies have found the same beneficial effects in hyperglycemic rats' hearts and kidneys. 16,17 Emerging evidence demonstrates the neuroprotective effects of melatonin in normoglycemic animals with focal cerebral ischemia.…”
Section: Introductionmentioning
confidence: 76%
“…Melatonin can easily pass through the blood‐brain barrier and be tolerated in a wide range of doses without toxicity 12 . Of note, melatonin protects against ischemia‐reperfusion injury in the kidney, intestine, and heart in normoglycemic animal models 13–15 . Recent studies have found the same beneficial effects in hyperglycemic rats' hearts and kidneys 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…SOD protects cells from oxidative stress by converting the superoxide anion radical (O 2 – ) radicals to O 2 and H 2 O 2 [ 17 , 41 , 42 ]. In a recent study, SOD level was reported to increase after abdominal surgery [ 43 ]. GSH prevents oxidative damage by reducing ROS such as free radicals, peroxides, and lipid peroxides [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…GSH is the major antioxidant sensitive to intracellular ROS ( Yu et al, 2019 ). SOD and CAT are the first line of defense against oxidative stress by directly scavenging ROS in the defense system ( Ozkan et al, 2018 ; Yu et al, 2019 ). MDA is the final product of lipid peroxidation and a biomarker indicating the level of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%